Women in supramolecular chemistry: collectively crafting the rhythms of our work and lives in STEM. (Bristol University Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Women in Science, Technology, Engineering and Maths (STEM) disciplines face a gender gap that has been exacerbated during COVID-19. Drawing on research carried out by the Women in Supramolecular Chemistry (WISC) network, this essential book sets out the extent to which women working in STEM face inequality and discrimination. The authors use approaches more commonly associated with social sciences, such as creative and reflective research methods, to shed light on the human experiences lying behind scientific research. They share fictional vignettes drawn from research findings to illustrate the challenges faced by women working in science today. Additionally, they show how this approach helps make sense of difficult personal experiences and to create a culture of change. Offering a path forward to inclusivity and diversity, this book is crucial reading for anyone working in STEM.